The Study of Citrus’s Fibers Production for Power Bar and the Effect on Consumer’s Acceptance - Somrajlichinda, Nathamon (Journal of Food Health and Bioenvironmental Science, 2023)
This research is a study into the production of citrus fiber from 4 citrus plants: pomelo, tangerines, sweet orange, and limes. Produced dietary fibers were analyzed and the amounts of fiber were found to be 58.21 %, 48.45 %, 44.90 %, and 41.70 % in the pomelo, tangerines, sweet orange, and limes, respectively. According to appropriate material supply, fiber amounts, and the production time, fiber from selected tangerines was added to a power bar product. The ingredients of the power bars were investigated and controlled based on the standard of Acceptable Macronutrient Distribution Ranges (AMDR). The nutrient energy of the power bar was analyzed, and the results showed a calorie ratio of carbohydrate 48.02 %, protein 11.40 %, and fats 40.56 %. These power bars were produced with the amount of citrus dietary fiber being added in the ratio of 5 %, 7 %, and 10%. The result showed that the power bar containing 5 % ratio of citrus’s fiber had average scores for the highest of all aspects. Appearance had an average score of 8.60, color with an average score of 8.66, taste with an average score of 8.73, texture had an average score of 8.46, and finally, overall acceptance had an average score of 8.73. The amount of orange peel added to the energy bar at 7 % ratio and 10 % ratio are different from 5 % ratio with a 95 % confidence in statistics.